2011
DOI: 10.14411/eje.2011.072
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative defence of brood in Nicrophorus quadripunctatus (Coleoptera: Silphidae)

Abstract: Abstract.A positive correlation between the parental effort of a male and female should promote stable biparental care. In order to prevent infanticide male and female burying beetles are said to guard against intruders cooperatively and the presence of a male partner is said to increase the probability of successful defence. However, this hypothesis is supported only by indirect evidence. In this study this hypothesis is tested by direct observation. Whether the intruder was male or female, contests between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…Biparental cooperation can repel intruder beetles [20]. In the present experiments, no females attacked the intruder males, and thus, biparental cooperative defence did not occur.…”
Section: Discussioncontrasting
confidence: 40%
See 3 more Smart Citations
“…Biparental cooperation can repel intruder beetles [20]. In the present experiments, no females attacked the intruder males, and thus, biparental cooperative defence did not occur.…”
Section: Discussioncontrasting
confidence: 40%
“…The results of the present study also indicated that larger males are more likely to win a male-male contest. However, it has been reported that smaller Nicrophorus individuals can repel a larger intruder [20,21]. Biparental cooperation can also affect the fate of contests; a male-female pair can usually repel a larger male intruder [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mayr, 1884 Kaptein et al, 2005 Sehirus cinctus Palisot, 1811 Kölliker et al, 2005Forficula auricularia L., 1758Mas et al, 2009Mas and Kölliker, 2011 Maynard Smith, 1982Houston et al, 2005Harrison et al, 2009McNamara et al, 1999Houston and McNamara, 1999Royle et al, 2010Tallamy, 1994 1 Onthophagus taurus Schreber 1759 Hunt and Simmons, 2002Fetherston et al, 1990Rauter and Moore, 2004Ward et al, 2009? Smiseth et al, 2005 Smiseth and Moore 2004b Suzuki and Nagano 2009 N. quadripunctatus Kraatz, 1877Harrison et al, 2009Houston et al, 2005Harrison et al, 2009Fetherston et al, 1990Rauter and Moore, 2004Mock and Parker, 199724 Smiseth and Moore, 2006Smiseth et al, 2007aSmiseth et al, 2007bTrumbo, 1990b Cylindrocaulus patalis Lewis, 1883 and Parker, 2008Smiseth et al, 2010Trumbo, 1990a, 2007Robertson, 1993Trumbo and Valletta, 2007Müller et al, 2003Suzuki, 2011Steiger et al, 2007Steiger et al, 2009 N. orbicollis Scott et al, 2008 Howard Costa, 2006…”
mentioning
confidence: 99%